Methods for defining the binary coal mixture composition in the pulverized coal-fired boiler - Євген, Пістун; Степан, Мисак; Галина, Матіко; Yevhen, Pistun; Stepan, Mysak; Halyna, Matiko (Printing Center of lviv Politechnic Publishing House, 2017)
Розглянуто методи визначення часток складових вугільної суміші, що спалюється, в паливні котла на теплових електричних станціях. Запропоновано непрямі методи визначення часток складових суміші двох марок вугілля, що ґрунтуються на наявній інформації щодо якісних характеристик вугілля. За першим методом склад вугільної суміші визначають за значеннями вмісту летких речовин на горючу масу вугільної суміші та кожної із марок вугілля, з яких складається суміш. У другому методі частку двох марок вугілля знаходять за нижчою теплотою згорання вугільної суміші та нижчою теплотою згорання вугілля двох марок, що входять до складу суміші. Виконана оцінка невизначеності результату визначення часток складових суміші двох марок вугілля пилосистеми котла за допомогою розроблених методів.

The paper deals with the methods for defining the composition of the coal mixture burnt in boilers at combined heat and power plants. Indirect methods for defining the proportions of the two grades of coal in the mixture based on the available information on the quality characteristics of the coal are proposed. According to the first method the coal mixture composition is determined based on the values of volatile substances content in the combustible mass of the coal mixture and of each grade of coal making up the mixture. The second method uses the lower combustion heat of the coal mixture and lower combustion heats of the two grades of coal that the mixture consists of. The uncertainties of the results obtained by the developed methods are evaluated.
Методи визначення часток складових суміші двох марок вугілля пилосистеми котла
Keywords: методи; вугільна суміш; склад суміші; котел; пилосистема; невизначеність; coal mixture; mixture composition; boiler; pulverized coal system; uncertainty